2010
DOI: 10.2522/ptj.20090217
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Exercising Among People With Osteoarthritis: A Phenomenological Study

Abstract: Increased knowledge and understanding of the factors influencing exercise behavior in people with OA can help physical therapists and other health care professionals support them in initiating and maintaining a healthy exercise routine and, consequently, achieving a better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 38 publications
12
102
0
2
Order By: Relevance
“…The interview results of our study also highlighted other factors that facilitated or inhibited exercise and physical activity similarly across all three treatment arms, and which may help explain the trial results. In line with previous research, 210,268 we found that a wide range of intrinsic (e.g. personal factors) and extrinsic (e.g.…”
Section: Worktream 3: Improving the Effectiveness Of Exercise For Ossupporting
confidence: 79%
“…The interview results of our study also highlighted other factors that facilitated or inhibited exercise and physical activity similarly across all three treatment arms, and which may help explain the trial results. In line with previous research, 210,268 we found that a wide range of intrinsic (e.g. personal factors) and extrinsic (e.g.…”
Section: Worktream 3: Improving the Effectiveness Of Exercise For Ossupporting
confidence: 79%
“…Studies have identified both internal and external facilitators and barriers to exercise (28,29,31). Internal factors include individual attributes such as motivation, personality, self-image, exercise attitude, exercise history, and disease knowledge, as well as personal experience.…”
mentioning
confidence: 99%
“…49 External barriers, those attributed to social and environmental-related factors, include access to resources such as safe exercise environments, transportation, disposable income, and exercise partners. Both internal and external barriers have been identified as real challenges to physical activity participation for persons with conditions managed by physical therapists, including osteoarthritis, 29 chronic pain, 1,21 low back pain, 16,19 and stroke. 36,45 There is limited research on interventions to change internal barriers to physical activity, and fostering long-term change in physical activity participation has had only partial success.…”
Section: T T Resultsmentioning
confidence: 99%